Two new species of the family Nippobodidae (Acari, Oribatida), including a description of the leg-folding process - Fernández, Néstor Alfredo (2018)
Nippobodes panemorfis sp. n. and Leobodes trypasis sp. n. are described by means of optical and Scanning ElectronMicroscopy (SEM) and compared to other congeners. The leg-folding process is described and illustrated.Nippobodes panemorfis sp. n. is characterised by interlocking, double hook-shaped, posterior prodorsalcondyle and anterior zone humeral apophysis; posterior prodorsal depression present. Tutorium a largelamina defining a pocket-shaped structure; bothridial opening ovoid, situated at the bottom of a U-shapedstructure; deep, rounded-ovoid anterior notogastral depression present; ten pairs of notogastral setae; csetae looped, dentate, sharply tipped. Marginal setae h3, p3 on large promontories, followed by deep Vshapedincision; notogaster completely surrounded by circumgastric depression; lateral genital zone withlocking structure constituted by longitudinal cuticular elevation, with promontories and a parallel furrowinvolved in the leg-folding process; genital plate smaller than anal plate.Leobodes trypasis sp. n. is characterised by: the presence of posterior prodorsal depression and anteriornotogastral depression; bridge-shaped anterior prodorsal condyles; heart-shaped frontal prodorsal orifice;ten pairs of notogastral setae; posterior prodorsal condyle and humeral condyle interlocked, formingdouble hook-like structure; circumgastric furrow surrounding entire notogaster; setae lp, h2, h1 situated onshallow medial furrow; notogastral setae lm, lp, h1, h2 medially aligned; p1, p2, p3, h3 marginally situated.Legs I-IV, tutorium, pedotectum I, and pedotectum II involved in leg folding which is inferred to be aprotection mechanism.